Delivering the 'D' in transit-oriented development: Examining the town planning challenge - Carey Curtis (Journal of Transport and Land Use)
Transit oriented development (TOD) provides a central focus where land use planning and transport planning should strongly interact. The core question in this paper is whether the conventional planning system can implement TOD. Of particular interest is whether state planning policy for TOD is articulated through to local government planning policy and if it is, does implementation occur as evidenced by development change on land around railway stations. A series of research investigations include policy analysis and development mapping around Perth metropolitan railway stations. While State policy for TOD is longstanding, its articulation to the local level is inconsistent. Forward development planning for TOD has faltered, especially in relation to new station precincts on new railways. Development change through the conventional planning system has been slow despite long policy lead times. There are significant actions needed if development in station precincts is to be delivered.